Sentence Composition: Language Map of Beginner Writers - Shalawati Shalawati; Sitti Hadijah (UIR Press, 2020)
This research was initiated to study the pattern of sentences written by students who were considered as beginner in their writing work. The further aim upon the study was to see what majority of the group approaches in developing their sentences in regards of their linguistic process as well as their idea organization. In respond to its initial drives, this study was approached in qualitative manner. There were 30 papers were examined and analyzed to synthesize the working approaches by the writers at common system and the attention was brought the individual sentence character and ideas organization throughout sentences and paragraphs. The findings suggest that the sentences were relatively good on language part but once the writing topics require their opinion and existing information, it started to decrease its quality. In such of writing, overgeneralized ideas and illogical structures are common. Therefore, since the writers were beginners, this research suggests supporting system that help the writers cope with their language barriers through introducing language on more complex language forms and together with practices. In addition to this, to support writers as the task environment increases reading materials are essential to help them build a more thoughtful writing piece.